UNIVERSAL VALUES OF THE EUROPEAN UNION AS LEGAL STANDARDS IN LEGISLATIVE ACTIVITY IN UKRAINE (THEORETICAL-LEGAL ASPECT) - Artem Beresten (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право»)
This article is dedicated to a scientific-practical analysis of the provisions of the Law of Ukraine dated August 24, 2023, No. 3354-IX "On Legislative Activity" (hereinafter referred to as the Law), which regulates social relations in the sphere of legislative activity in Ukraine in the context of Eurointegration. Specifically, it addresses activities and regulation related to planning, development, adoption (issuance), application of normative legal acts, and legal monitoring. The article provides an analysis of individual provisions of the law, legal and organizational principles of legislative activity, methods, and the sequence of its implementation, as well as the elimination of gaps and conflicts in normative legal acts.